ANALISIS MOTIVASI PETERNAK DALAM USAHA PETERNAKAN KAMBING PADA MASYARAKAT PESISIR DI KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Muh Al Ardi Malawat; Pieter Melianus Ririmase; George Semuel J. Tomatala (MARSEGU : Jurnal Sains dan Teknologi, 2026)
This study aims to analyze the motivations of farmers in goat farming among coastal communities in Leihitu District, Central Maluku Regency. The sample in this study was taken using purposive sampling, totaling 30 people. The data collection techniques used were interviews, questionnaires, and documentation. The type of data used in this study was quantitative data. Measurement of the community's interest in goat farming was conducted using a Likert scale. The results obtained from this study show that most farmers are aged 34-46 years with a good category, the last education level of most farmers is high school graduates in the good category, the majority of farming experience is 5-10 years in the good category, the number of family members in the farmer households is 5-6 people in the good category, the number of livestock is 11-20 animals in the moderate category, the farmers' income is 6-10 million IDR per month in the good category, and the farmers' land ownership.